Gangguan Keterlambatan Bicara Pada Anak di PAUD Inklusi Nur Ramadhan Gambut: Speech Delay Disorders in Children at PAUD Inclusion Nur Ramadhan Gambut - Yuliani, Novi Dwi; Puteri, Erlin Nur Rizky Amalia; Rahmaniah, Rahmaniah; Aminah, Siti; Nordiansyah, Nordiansyah; Zaini, Muhammad; Azmy, Fikri Fuadi (Nusantara Journal of Education and Social Science, 2025)
This research is driven by the fact that school-age children with language or speech delays are at an increased risk of developing learning and reading disabilities, which can lead to challenges in reading and writing. This research aims to find out how the language disorders experienced by some learners from the Nur Ramadhan Gambut Inclusive PAUD located in the Sejahtera Mandiri Asri Gambut Complex Kertak Hanyar allow researchers to find out how these learners interact in their daily activities. This research employs qualitative methods to explore phenomena by analyzing a series of data. Data collection is conducted through observation and interviews. The research identifies two key factors: (1) poor communication and (2) birth defects.